Microsatellite analysis sheds light on the conservation of Dyckia brevifolia Baker - Liana Bittencourt Petrarca; Joana Nascimento Oliveira Zeist; Suelen Martinez Guterres; Juliana Machado Ferreira; Yohan Fritsche; Tiago Montagna; Valdir Marcos Stefenon (Brazilian Journal of Botany, 2026)
Dyckia brevifolia is a riparian bromeliad endemic to southern Brazil. Despite the endangered status of this species, no genomic resources are available to aid conservation initiatives. This study describes the investigation of the genetic diversity and structure of D. brevifolia populations using newly neutral, species-specific nuclear microsatellite markers developed through genome skimming. Genotyping thirty individuals from three populations with nine generated microsatellite markers revealed low levels of allelic and genetic diversity ( A = 2.56 and He = 0.39, Ho = 0.19) and high fixation index ( f = 0.46), indicating significant inbreeding levels. Principal coordinates analysis suggested the occurrence of gene flow directed by river current, favoring downstream populations, which evidences hydrochorous dispersal of propagules. These primary data using molecular markers provide the basis for designing conservation strategies to ensure the maintenance of gene flow and genetic variability in the fragmented populations of D. brevifolia .

A reference genome for Plinia edulis: expanding the pharmacological and nutraceutical potential of a neglected brazilian tree species - Valdir Marcos Stefenon; Thiago Sanches Ornellas; Yohan Fritsche; Suelen Martinez Guterres; Ingrid Lohani Degering Brand; Ana Kelly de Sousa Silva; Fernando Joner (Molecular Genetics and Genomics, 2025)

Biotechnological potential of pineapple-Serendipita co-cultivation for salinity resilience in agriculture - Danielle da Silva; Ana Kelly de Sousa Silva; Fernanda Vidigal Duarte Souza; Yohan Fritsche; Valdir Marcos Stefenon (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A four steps protocol for in vitro propagation of Eugenia uniflora L. (Myrtaceae) - Lucas Barasuol Franco; Bruna Ronchi Hermann; Yohan Fritsche; Valdir Marcos Stefenon (Genetic Resources and Crop Evolution, 2024)

What’s in my Pot? Six Colletotrichum Species Causing Anthracnose in Brazilian Pecan Orchards - Tales Poletto; Yohan Fritsche; Vinícius Spolaor Fantinel; Marlove Fátima Brião Muniz; Ricardo Harakava; Valdir Marcos Stefenon (Current Microbiology, 2024)

Cell division and dynamics in global DNA methylation associated with radicle protrusion in Trichocline catharinensis seeds (Asteraceae) - Ana P. Lando; Daniela Goeten; W. G. Viana; Yohan Fritsche; Miguel P. Guerra; N. Steiner (Acta Physiologiae Plantarum, 2024)

Somatic embryogenesis from young spikelets of the giant bamboo Dendrocalamus asper (Schult f.) Backer ex Heyne - Thiago Sanches Ornellas; Yohan Fritsche; Edison Cardona-Medina; Miguel Pedro Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Ploidy mosaics: does endopolyploidy in explants affect the cytogenetic stability of orchids regenerated from PLBs? - Yohan Fritsche; Thiago Sanches Ornellas; Valdir Marcos Stefenon; Miguel Pedro Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Serendipita restingae sp. nov. (Sebacinales): an orchid mycorrhizal agaricomycete with wide host range - Yohan Fritsche; Morgana E. Lopes; Marc-André Selosse; Valdir M. Stefenon; Miguel P. Guerra (Mycorrhiza, 2021)